2016
DOI: 10.1002/dta.1959
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of 24 CYP2D6 allelic isoforms on the metabolism of methadone

Abstract: CYP2D6 is an important member of the cytochrome P450 (CYP450) enzyme super family, with at least 100 CYP2D6 alleles being previously identified. Genetic polymorphisms of CYP2D6 significantly influence the efficacy and safety of some drugs, which might cause adverse effects and therapeutic failure. The aim of this study was to clarify the catalytic activities of 24 CYP2D6 alleles on the oxidative in vitro metabolism of methadone. Reactions were incubated with 50-2000  µM methadone for 30 min at 37 °C and termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…[11][12][13] However, our previous study showed that CYP2C19 and CYP3A4 can contribute, to some extent, to this pathway for the metabolism of nebivolol 4-hydroxylation. 11 It seems that several CYP450 enzymes may be involved in nebivolol metabolism as well as some drugs, such as fluoxetine, 14,15 methadone, 16,17 and citalopram. 18,19 Most importantly, CYP2C19 polymorphisms are deeply Table S1 in the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] However, our previous study showed that CYP2C19 and CYP3A4 can contribute, to some extent, to this pathway for the metabolism of nebivolol 4-hydroxylation. 11 It seems that several CYP450 enzymes may be involved in nebivolol metabolism as well as some drugs, such as fluoxetine, 14,15 methadone, 16,17 and citalopram. 18,19 Most importantly, CYP2C19 polymorphisms are deeply Table S1 in the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%
“…Data from in vitro studies suggested that CYP3A4, CYP2D6, CYP2C8, CYP2C9, and CYP2C19 play a role in the metabolism of methadone to its active metabolite, 2‐Ethyl‐1,5‐dimethyl‐3,3‐diphenylpyrrolinium (EDDP) . Methadone is primarily metabolized by CYP3A4, and to a lesser extent by CYP2C8, CYP2C9, CYP2C19, and CYP2D6 . Since methadone is a substrate of CYP enzymes, the changes of CYP activities may influence the pharmacokinetic profile of methadone, involving the concentration, clearance and bioavailability of methadone.…”
Section: Introductionmentioning
confidence: 99%
“…Methadone maintenance treatment (MMT) is widely used to reduce the harms of opioid use disorder . Methadone is primarily metabolized via N‐demethylation to an inactive metabolite, 2‐ethylidene‐1,5‐dimethyl‐3,3‐diphenylpyrrolidene (EDDP) . In vitro metabolic investigations, using human liver microsomes or recombinant cytochrome P450 enzymes, suggested that CYP2D6, 3A4, and 2C19 played an important role in the metabolism of methadone .…”
Section: Introductionmentioning
confidence: 99%
“…2 Methadone is primarily metabolized via N-demethylation to an inactive metabolite, 2-ethylidene-1,5dimethyl-3,3-diphenylpyrrolidene (EDDP). 3 In vitro metabolic investigations, using human liver microsomes or recombinant cytochrome P450 enzymes, suggested that CYP2D6, 3A4, and 2C19 played an important role in the metabolism of methadone. [3][4][5] In vivo investigations also suggested that CYP3A4 and CYP2C19 genetic polymorphism, influencing methadone dose and tolerance, contributed to the methadone poor metabolizer phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation